PYONEPHROSIS FOLLOWING OVARIOHYSTERECTOMY IN A BITCH: CASE REPORT. - APPARICIO, M.; VICENTE, W. R. R.; FARIAS, A.; COVIZZI, G. J.; RIBEIRO, A. P. C.; GADELHA, C. R. F. (Ars Veterinaria, 2008)
A five-year old cross breed bitch was presented at the Veterinary Hospital